Dropping beats - Lessore, Nathanael (Little, Brown and Company, 2025)
Aspiring young rapper Shaun 'Growls' Thompson navigates through embarrassing incidents, family troubles, and friendship challenges, finding support from a new friend and ultimately hatching a plan to save his family from eviction.